XUANKUN LI, ZHU LI& DING YANG (2013) Two new species of Amblypsilopus Bigot with a key to species from Vietnam (Diptera: Dolichopodidae). Zootaxa, 3630(3): 549–560. - Li, Xuankun; Li, Zhu; Yang, Ding (Zootaxa, 2013)
Running title on page 550 forward should read as: LI ET AL. and NEW AMBLYPSILOPUS FROM VIETNAM